PEMANFAATAN AUGMENTED REALITY SEBAGAI MEDIA PROMOSI KAMPUS POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG - Nugraha, Estu; Septiandi, Recky; Josi, Ahmat; Andriyanto, Sidhiq (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2025)
The development of technology today is advancing at a rapid pace, particularly in the field of information technology. One of the latest advanced and modern information technologies, such as Augmented Reality (AR), has been widely used as a medium for creating 3D objects, such as objects and buildings. This study aims to explore the use of AR for creating promotional and campus introduction media that can accurately represent the physical forms of buildings and facilities at the Bangka Belitung State Polytechnic of Manufacturing, a vocational higher education institution in Indonesia specializing in manufacturing. This media is developed as an Android-based application and can be accessed via Virtual Reality. The method used in this study is the Multimedia Development Life Cycle (MDLC) method. The research results show that the feasibility test score obtained was 82.5%, categorized as highly feasible. Based on these results, it can be concluded that the application was successfully implemented using AR technology and functions effectively.